"An Apple of Discord": The Island of Al-Zorah, 1843–1945. Issue 2 (3rd July 2018) - Morton, Michael Quentin
Abstract: Based on an extensive study of archival records, this article shows how a series of episodes in the history of the Trucial Coast — today's United Arab Emirates (UAE) — helped to shape the direction of the area's history. At face value, the island of al-Zorah appeared to have little to offer, but it nevertheless figured in the ambitions of the Wahhābīs, local rulers and the British, all of whom coveted it for one reason or another; the outcome of their struggles helped to set the seal on the future configuration of the UAE. While the article provides a valuable insight into Great Britain's role in the area, it also reveals regional rivalries and inter-tribal tensions that still exist in the region today. However, the coming together of the UAE and Saudi Arabia, and their need to show solidarity in the face of current challenges, have obscured the historical differences that the story of al-Zorah represents.